Aplikasi Pencarian Toko UMKM Terdekat Berbasis Android Menggunakan Api Google Maps - Anam, Khairil; Arif, Isturom; Farkhan, M. (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2024)
The role of MSMEs is very important in increasing economic development in a region, especially MSMEs for grocery stores. However, there are several obstacles to MSME grocery store operators in Sidoarjo Regency, one of which is the minimal use of E-Commerce for the development of their grocery store business, making it difficult for small shop operators to increase production volumes to achieve greater turnover. Basic food stores in Sidoarjo district are unable to compete with large stores that have online websites such as Indomaret, Alfamart which can make it easy to find products and carry out shopping transactions for customers. One solution to overcome this problem is to create an Android-based application for MSMEs for basic food stores in Sidoarjo Regency using the Google Maps API. With this research, it is greatly facilitated for the community in carrying out buying and selling transactions, starting from payment, time and energy expended. With research that utilizes Google Maps Fire Technology, the people of Sidorejo can easily search for the products they want from grocery stores in the surrounding area and make it easier for shop owners to market their products, so that by making this application it can make it easier to carry out shopping activities and become one of them. a driving force in the community economy.